2022
DOI: 10.3390/biomedicines10071583
|View full text |Cite
|
Sign up to set email alerts
|

The Sesquiterpene Lactone Cynaropicrin Manifests Strong Cytotoxicity in Glioblastoma Cells U-87 MG by Induction of Oxidative Stress

Abstract: Cynaropicrin has shown a wide range of pharmacological properties, such as antitumor action. Here, we showed the inhibitory effect of Cyn on human glioblastoma cell U-87 MG growth. According to the IC50 values, Cyn 4, 8 and 10 µM displayed a significant cytotoxicity, as confirmed by the cell count and MTT assay. Furthermore, Cyn completely abolished the ability of U-87 MG to form colonies and induced drastic morphological changes. Interestingly, pretreatment with ROS scavenger N-acetylcysteine 3 mM reversed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…The fact that the expression of Beclin1 and P62, two autophagy markers, did not change after treatment and the combination of cynaropicrin with either bafilomycin A1 or rapamycin did not significantly alter the sensitivity of AMO1 to cynaropicrin refuted this assumption as well. Unexpectedly, our findings were contradictory to previously published research that suggested that cynaropicrin-induced cytotoxicity is associated to either apoptosis or autophagy [ 76 , 80 , 81 ]. In an attempt to decipher the mode of cell death induced by cynaropicrin in more detail, we studied the effect of cynaropicrin on the mitochondrial membrane potential as mitochondria are the cellular powerhouse and important regulators of cell death [ 82 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The fact that the expression of Beclin1 and P62, two autophagy markers, did not change after treatment and the combination of cynaropicrin with either bafilomycin A1 or rapamycin did not significantly alter the sensitivity of AMO1 to cynaropicrin refuted this assumption as well. Unexpectedly, our findings were contradictory to previously published research that suggested that cynaropicrin-induced cytotoxicity is associated to either apoptosis or autophagy [ 76 , 80 , 81 ]. In an attempt to decipher the mode of cell death induced by cynaropicrin in more detail, we studied the effect of cynaropicrin on the mitochondrial membrane potential as mitochondria are the cellular powerhouse and important regulators of cell death [ 82 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, in addition to the chemopreventive effects of phytosterols (Salehi et al, 2021), a number of studies have shown that some phytosterols (Qi et al, 2013) and oxidized phytosterols (oxyphytosterols) (Hovenkamp et al, 2008;Koschutnig et al, 2009) are cytotoxic to cancerous and normal cells. β-Sitosterol has shown apoptosis in HAAE-2 (human abdominal aorta endothelial cells), inducing caspase-3 activity in the cells that corresponded the DNA fragmentation analysis in a terminal uridine deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick-end labeling (TUNEL) study (Rubis et al, 2008). On the other hand, since cholesterol metabolism is deregulated in these tumors, potentially toxic cholesterol analogues and phytosterol derivatives, and LXRs (Liver X Receptors) might be beneficial in metabolic treatments to suppress glioblastoma tumorigenicity, which can lead to glioblastoma cell death (Ahmad et al, 2019;Sassi et al, 2021).…”
Section: Sterols and Phytosterolsmentioning
confidence: 83%
“…Cynaropicrin exerts this effect on U-87 MG through inducing intracellular ROS generation, reducing MM, and promoting the release of cytochrome C into the cytoplasm of these cancer cells. It also led to the activation of caspase 3 and caspase 9, suggesting the involvement of the mitochondrial pathway of apoptosis in cynaropicrin effects on U-87 MG cells ( Rotondo et al, 2022 ). Liu T. et al (2019) conducted a study to evaluate the effect of cynaropicrin on the Hela human cervical cancer cell line.…”
Section: Sesquiterpene Lactones With Pro-apoptotic Activities In Cancermentioning
confidence: 99%